2004
DOI: 10.1242/jeb.01076
|View full text |Cite
|
Sign up to set email alerts
|

Hypergravity from conception to adult stage: effects on contractile properties and skeletal muscle phenotype

Abstract: SUMMARY This study examined the effects of an elevation of the gravity factor(hypergravity – 2 g) on the molecular and functional characteristics of rat soleus and plantaris muscles. Long Evans rats were conceived, born and reared (CBR) continuously in hypergravity conditions until the age of 100 days. Whole muscle morphological parameters, Ca2+activation characteristics from single skinned fibers, troponin (Tn) subunit and myosin heavy (MHC) and light (MLC) chains isoform compositions were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Rats born and reared in hypergravity showed changes in the morphological and contractile properties (Picquet et al 2002;Bozzo et al 2004). At the contrary, unloading conditions atrophied skeletal muscles with different degrees according to the muscle type and muscle function (Picquet et al 1998;Fitts et al 2000).…”
Section: Preliminary Results On the Long Term Effects Of An Early Expmentioning
confidence: 99%
See 2 more Smart Citations
“…Rats born and reared in hypergravity showed changes in the morphological and contractile properties (Picquet et al 2002;Bozzo et al 2004). At the contrary, unloading conditions atrophied skeletal muscles with different degrees according to the muscle type and muscle function (Picquet et al 1998;Fitts et al 2000).…”
Section: Preliminary Results On the Long Term Effects Of An Early Expmentioning
confidence: 99%
“…A possible explanation for this difference was the increased proportion of slow fibres in postural muscles. Previous studies showed that the morphological and contractile properties of postural muscles shifted to a slower type in rats born and reared in hypergravity during 100 days (Picquet et al 2002;Bozzo et al 2004). It can be supposed therefore that the exposition to hypergravity during a shorter time windows of the early motor development sufficed to definitely shift the muscles typology to a slower type, that offers a better resistance to fatigue and could counter balance some deleterious effects related to ageing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are in agreement with previous data. Indeed, lower birth weights have been reported in hypergravity-raised rats1314. Reduced pup weight could be explained by the higher energy expenditure induced in mothers by the hypergravity environment.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the composition of these contractile proteins are accepted as one of the phenotypic modifications related to skeletal muscle atrophy (Stevens et al 2000;Bozzo et al 2003). Some authors, using various experimental conditions (Bozzo et al 2003;Bozzo et al 2004;Stevens et al 2004), reported that the alterations in myosin heavy chain (MHC) isoforms are qualitatively similar and correspond with those in MLC isoforms. Our results (Fig.…”
Section: Discussionmentioning
confidence: 99%